Pola-Pola pada Segitiga Pascal dan Pembuktiannya - Untung Trisna Suwaji (Idealmathedu: Indonesian Digital Journal of Mathematics and Education, 2020)
Pascal's triangle has a variety of interesting patterns. This article discusses some of the patterns that might be found in Pascal's triangle and their proofs. In the teaching and learning process, teacher may invite students to observe these patterns, try the patterns to make generalization, make conjecture, prove the conjecture, and communicate the process to others. This procedure is appropriate with the teaching and learning process suggested in the Indonesian 2013 Curriculum.